STRATEGI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Erisma adelia; Hidayati; Elly Fatmawati; Moh.Faizin (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Islamic Religious Education (PAI) plays a crucial role in shaping students’ character and morality through the internalization of Islamic values in everyday life. PAI learning is not only oriented toward cognitive understanding, but also toward the development of attitudes, behavior, and skills that reflect noble character. However, the rapid growth of technology and digital transformation has created new challenges in the learning process. Conventional teaching methods such as lectures and memorization are considered less effective when they are not supported by strategies capable of influencing students’ real behavior in a sustainable manner. This study aims to explain the concepts of habituation and exemplary strategies in PAI learning and to analyze the effectiveness of integrating positive reinforcement in character building. The study employed a descriptive qualitative method with a literature study approach through content analysis of various relevant references on character education and PAI learning. The findings indicate that strong character formation requires consistent habituation, the presence of role models who can be emulated, and continuous positive reinforcement. The integration of these three strategies has proven effective in increasing intrinsic motivation, fostering moral awareness, building discipline, and encouraging students’ independent learning holistically. Therefore, habituation, exemplary behavior, and positive reinforcement strategies can serve as effective approaches in strengthening the implementation of PAI learning that is relevant to educational needs in the era of digital transformation